(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with an issue of "value attitude to health" as an integrated system of the individual, selective relationships with different objects and matter of the environment, which finds manifestation in practical vital functions and health assessments. The author shows methods of developing values of health of students. This process includes involvement of student youth in physical culture and sports activities; the development of student’s awareness in the ways of using the relevant information; picking health systems and practices in the field of preservation and strengthening of health; increasing knowledge about connections between physical, mental and social health; awareness of health as a self-preservation ability; the formation of the value of a healthy lifestyle.